Meson mass spectrum in QCD2 't Hooft's model - Alexey Litvinov; Pavel Meshcheriakov (Nuclear Physics B)
We study the spectrum of meson masses in large Nc QCD2 governed by celebrated ‘t Hooft's integral equation. We generalize analytical methods proposed by Fateev, Lukyanov and Zamolodchikov to the case of arbitrary, but equal quark masses m1=m2. Our results include analytical expressions for spectral sums and systematic large-n expansion. We also study the spectral sums in the chiral limit and the heavy quark limit and find a complete agreement with known results.